Peace as an Event and Peace as Utopia: An Analysis on Mary Collins’ Ten Bells Street at War - Badri Prasad Pokharel, (Interdisciplinary Journal of Management and Social Sciences, 2025)
This paper analyses the plight and predicament of local residents of one locality in the East End of London’s Ten Bells Street where people are scared during the World War ll. Mary Collins’ novel Ten Bells Street at War is an account of three childhood friends who have been scattered due to the consequences of the war which had completely devastated the whole of Europe. People like Rose, Becky and Bernie have been living a terrific life under the shadow of Adolf Hilter’s tyranny and everyone is found to have been looking for an ultimate solution to regain the possibility of peace and solidarity in which all European and non-European, Christians and Jews etc. can live together as brothers and sisters. In this paper, I analyse the problems of scattered people due to the terrific consequences of the war based on different grounds: What consequences led the people to live away from their own family, friends and relatives? What is the cause behind their separation? Why have they been encountering unspeakable suffering while the war was in utmost peak? How can the issue of peace and solidarity be prevailed in the war-torn society? Can they live their life peacefully hereafter? Such questions are discussed using relevant peace and war theories.